1996
DOI: 10.1016/0014-5793(96)00225-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan‐binding properties of human serum hemopexin

Abstract: Hemopexin, the heme-binding serum glycoprotein, exhibits a complex electrophoretic pattern on two-dimensional immunoelectrophoresis on agarose gels into which hyaluronic acid is incorporated in the first and monospecific anti-hemopexin in the second dimension. This heterogeneity reflects a range of interactions of hemopexin isoforms with hyaluronic acid. Electrophoretic patterns of individual human sera greatly differ in their contents of hyaluronan-interacting hemopexin species. Hemopexin itself has no hyalur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…In particular, PRG4 has a hemopexin-like domain near the C-terminus. Purified hemopexin interacts with hyaluronan (HA), 12 suggesting that the hemopexin-like domain could also mediate PRG4 binding to HA present at or near the articular surface. In addition, lubrication studies have shown that HA and PRG4 act in concert to reduce friction, 13 supporting the possibility of molecular interaction between the two at the articular surface.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PRG4 has a hemopexin-like domain near the C-terminus. Purified hemopexin interacts with hyaluronan (HA), 12 suggesting that the hemopexin-like domain could also mediate PRG4 binding to HA present at or near the articular surface. In addition, lubrication studies have shown that HA and PRG4 act in concert to reduce friction, 13 supporting the possibility of molecular interaction between the two at the articular surface.…”
Section: Introductionmentioning
confidence: 99%
“…71 This finding was based on cloned complementary DNA corresponding to an abundant protein in a purified porcine liver fraction that exhibited hyaluronidase activity. Hrkal et al determined later 73 that human hemopexin does not possess hyaluronidase activity but that hyaluronidase, which is electrophoretically distinct from hemopexin, contaminated nearly half of their hemopexin preparations. Nevertheless, these authors found that a portion (10-60%) of their purified hemopexin could bind hyaluronic acid.…”
Section: Hemopexin As a Hyaluronidasementioning
confidence: 99%
“…Nevertheless, these authors found that a portion (10-60%) of their purified hemopexin could bind hyaluronic acid. In an agarose matrix, 73 the pattern of hemopexin-hyaluronic acid interaction exhibited microheterogeneity that varied from one serum sample to another as well as from one hemopexin preparation to another. Subsequently, however, purified hemopexin was found to be unable to bind hyaluronic acid in solution.…”
Section: Hemopexin As a Hyaluronidasementioning
confidence: 99%
See 1 more Smart Citation
“…25,38 The final solution was made in Tris buffer (pH 7.4). Heat-inactivated Hx was used as an inactive control as described previously.…”
Section: Reagentsmentioning
confidence: 99%